Lionfish (Pterois spp.) invade the upper-bathyal zone in the western Atlantic - Gress, E; Andradi-Brown, D; Woodall, L; Schofield, P; Stanley, K; Rogers, A (PeerJ, 2017)
Non-native lionfish have been widely recorded throughout the western Atlantic on both shallow and mesophotic reefs, where they have been linked to declines in reef health. In this study we report the first lionfish observations from the deep sea (>200 m) in Bermuda and Roatan, Honduras, with lionfish observed to a maximum depth of 304 m off the Bermuda platform, and 250 m off West End, Roatan. Placed in the context of other deeper lionfish observations and records, our results imply that lionfish may be found more widely in the 200-300 m depth range of the upper bathyal zone across the western Atlantic, but currently are under sampled compared to shallow habitats. We highlight the need for considering deep-sea lionfish populations in future invasive lionfish management.